2020
DOI: 10.1007/s00262-020-02738-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of sintilimab in combination with chemotherapy in previously untreated advanced or metastatic nonsquamous or squamous NSCLC: two cohorts of an open-label, phase 1b study

Abstract: Combining chemotherapy with immunotherapy improves the therapeutic outcome for first-line (1L) patients with advance nonsmall-cell lung cancer (NSCLC). Two cohorts of a phase 1b study (NCT02937116) aimed to evaluate the safety and efficacy of sintilimab, a PD-1 inhibitor, plus chemotherapy in 1L patients with nonsquamous and squamous NSCLC (nsqNSCLC/sqNSCLC); and to identify potential biomarkers for treatment response. Treatment-naïve patients with nsqNSCLC were enrolled and intravenously given sintilimab (200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Notably, the study revealed that PD-L1 expression, whether tumor proportion score (TPS) ≥ 1% or TPS < 1%, was not correlated with clinical response, and neither did the tumor mutation burden level (TMB). A high TCR Change (TCRC) clonality (> 1) was significantly associated with a better OS, while a low TCRC diversity (< 1) was closely related with a superior PFS [16].…”
Section: Lung Cancer Clinical Trialsmentioning
confidence: 99%
“…Notably, the study revealed that PD-L1 expression, whether tumor proportion score (TPS) ≥ 1% or TPS < 1%, was not correlated with clinical response, and neither did the tumor mutation burden level (TMB). A high TCR Change (TCRC) clonality (> 1) was significantly associated with a better OS, while a low TCRC diversity (< 1) was closely related with a superior PFS [16].…”
Section: Lung Cancer Clinical Trialsmentioning
confidence: 99%
“…Chen et al found that TMB could not predict treatment efficacy in advanced NSCLC patients treated with camrelizumab combined with apatinib 20 . Another study showed that TMB could not predict the efficacy of sintilimab combined with dual‐drug chemotherapy 21 . In addition, the definition of high TMB measured by different NGS detection platforms (different gene panels) might be different 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The phase 3 trial of sintilimab provided a longer 5.3 months of OS than docetaxel in patients with NSCLC whose disease progressed after chemotherapy ( Yang et al, 2020 ). Besides of monotherapy, sintilimab combined with either chemotherapy or anlotinib as the first-line treatment demonstrated encouraging antitumor activities ( Chu et al, 2021 ; Jiang et al, 2021 ) and combined with anlotinib, it showed a longer PFS of 15 months representing a novel chemotherapy-free regimen of NSCLC ( Zhang et al, 2021 ). The addition of sintilimab to chemotherapy also revealed promising efficacy and manageable safety in untreated gastric/gastroesophageal junction (GEJ) adenocarcinoma ( Jiang et al, 2020 ).…”
Section: Clinical Use Efficacy and Safetymentioning
confidence: 99%